2021
DOI: 10.4103/jfmpc.jfmpc_2140_20
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effects of Ketamine on Procedural Sedation and Analgesia (PSA) in the Emergency Department

Abstract: Background: Procedural sedation and analgesia (PSA) in the emergency department (ED) is mainly used for wound irrigation, reduction of fractures, and wound closure. Ketamine is one of the most commonly used drugs for PSA in the ED. The study was conducted in the ED of a large tertiary care hospital in southern India to evaluate the adverse effects of Ketamine on PSA. Materials and Methods: This is a prospective observational study performed in the ED for 6 months (Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…During the early stages of the SARS-CoV-2 (COVID-19) pandemic, ketamine was widely employed as an alternative sedative agent to allow for lung protective ventilation while patients received mechanical ventilation when other preferred agents were in short supply [ 2 ]. Although therapeutic use of ketamine is generally well tolerated and therefore widely used due to its limited safety profile compared to other sedatives [ 3 , 4 ], long-term use at high doses may warrant consideration of its toxicities [ 5 ]. While it is not well known that ketamine may be associated with liver toxicities, it has been reported that prolonged use, repeated use, or abuse of ketamine may lead to liver injury [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the early stages of the SARS-CoV-2 (COVID-19) pandemic, ketamine was widely employed as an alternative sedative agent to allow for lung protective ventilation while patients received mechanical ventilation when other preferred agents were in short supply [ 2 ]. Although therapeutic use of ketamine is generally well tolerated and therefore widely used due to its limited safety profile compared to other sedatives [ 3 , 4 ], long-term use at high doses may warrant consideration of its toxicities [ 5 ]. While it is not well known that ketamine may be associated with liver toxicities, it has been reported that prolonged use, repeated use, or abuse of ketamine may lead to liver injury [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine targets glutamate pathways, increasing the synaptic release of glutamate while also promoting neuroplasticity (Abdallah et al, 2018). Possible adverse side effects of ketamine include nausea, confusion, vomiting, and dysphoria (Dilip, Chandy, Hazra, Selvan, & Ganesan, 2021).…”
Section: Introduction Ketaminementioning
confidence: 99%